2001
DOI: 10.1046/j.1472-765x.2001.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral Bacillus coagulans administration on the density of vancomycin-resistant enterococci in the stool of colonized mice

Abstract: Aims: A mouse model of vancomycin‐resistant enterococcus (VRE) stool colonization was used to study the effect of Bacillus coagulans, a biotherapeutic agent, on the density of colonization. Methods and Results: VRE‐colonized mice received orally administered B. coagulans (107 cfu) or saline daily for four days. For one VRE strain, the density of VRE at one and four days after treatment was 1·4 log10cfu g−1 lower in experimental vs. control mice (P=0·03), and 35% of experimental vs. 0% of control mice had no d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…The VRE intestinal colonization experimental model was adapted from Donskey et al (7). Daily subcutaneous administration of clindamycin (1.4 mg/day) for 5 days was used to disrupt the intestinal microbiota as necessary to induce the VRE infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The VRE intestinal colonization experimental model was adapted from Donskey et al (7). Daily subcutaneous administration of clindamycin (1.4 mg/day) for 5 days was used to disrupt the intestinal microbiota as necessary to induce the VRE infection.…”
Section: Methodsmentioning
confidence: 99%
“…No recurrence was observed. Donskey et al (7) showed that a strain of Bacillus was able to reduce the fecal VRE concentration, but they did not implicate the production of a bacteriocin. Although the bacteriocin-producing strains are able to reduce the densities of VRE populations following an infection facilitated by clindamycin, these strains have no effect on the total Enterococcus spp.…”
Section: Fig 4 Changes In the Densities Of Total Vancomycin-resistantmentioning
confidence: 99%
“…The stools were collected periodically at six hour intervals up to 48 hours and subjected for enterococci colonization density study. 9 …”
Section: Model-dependent Methodsmentioning
confidence: 99%
“…7 To be therapeutically active, probiotics must arrive in the intestine alive and in sufficient numbers which is suggested at 10 6 -10 storage requirements during transportation and storage. [7][8][9][10][11][12] After their consumption, the hydrolytic enzymes, the acidic conditions of stomach, and the bile salts in the gastrointestinal (GI) tract also adversely affect the viability of probiotics. 7,[12][13][14][15] Various approaches such as the addition of different growth promoters, manipulation of fermentation and storage conditions of the food carriers, careful selection of the culture organisms according to their interrelationships and acid-bile resistance, and employing microencapsulation technology have been investigated to improve the amount of viable cells arriving in the intestine.…”
Section: Introductionmentioning
confidence: 99%
“…It is a good candidate for probiotic use, produces organic acids and possesses the capacity to sporulate. It secretes a bacteriocin, coagulin, which has activity against a broad spectrum of enteric microbes [15][16][17]. Bacillus subtilis is also a Gram-positive, lactic acid-forming bacterial species.…”
Section: Introductionmentioning
confidence: 99%